A Deposit of Early Medieval Iron Objects from Scraptoft, Leicestershire. (1st November 2013) - Leahy, Kevin
Abstract : A DEPOSIT OF FIVE iron objects found at Scraptoft, near Leicester, is interesting for the range of activities represented: woodworking, cultivation, harvesting and warfare. The objects are described and their dating discussed together with possible reasons for their deposition. Hoards of early medieval tools and weapons are well known in Britain, but iron objects seem surprisingly common on what appear to be Anglo-Saxon rural sites. The possibilities of ritual deposition and of these hoards symbolically representing the Anglo-Saxon economy are also considered.